Ethylene‐induced microtubule reorientation is essential for fast inhibition of root elongation in Arabidopsis. Issue 9 (30th June 2018) - Wang, Yichuan; Ji, Yusi; Fu, Ying; Guo, Hongwei
Abstract: Microtubule reorientation is a long‐standing observation that has been implicated in regulating the inhibitory effect of ethylene on axial elongation of plant cells. However, the signaling mechanism underlying ethylene‐induced microtubule reorientation has remained elusive. Here, we reveal, by live confocal imaging and kinetic root elongation assays, that the time courses of ethylene‐induced microtubule reorientation and root elongation inhibition are highly correlated, and that microtubule reorientation is required for the full responsiveness of root elongation to ethylene treatment. Our genetic analysis demonstrated that the effect of ethylene on microtubule orientation and root elongation is mainly transduced through the canonical linear ethylene signaling pathway. By using pharmacological and genetic analyses, we demonstrate further that the TIR1/AFBs‐Aux/IAAs‐ARFs auxin signaling pathway, but not the ABP1‐ROP6‐RIC1 auxin signaling branch, is essential for ethylene‐induced microtubule reorientation and root elongation inhibition. Together, these findings offer evidence for the functional significance and elucidate the signaling mechanism for ethylene‐induced microtubule reorientation in fast root elongation inhibition in Arabidopsis . Abstract : In this study, we reveal by a combinatorial approach the signaling mechanism and physiological significance of the long standing observation of ethylene‐induced microtubule reorientation in rapid inhibition of Arabidopsis root elongation. Particularly, we demonstrate the importance of auxin signaling module TIR1/AFBs‐Aux/IAAs‐ARF7/19, but not ABP1‐ROP6‐RIC1, for this rapid ethylene response.